The DotDitty Bag / Mimi Wahidah Mohd Radzi - Mohd Radzi, Mimi Wahidah (2020)
The name of the company is The DotDitty Sdn. Bhd. which the name is also dedicated to the attractive polkadot design for our ditty bags. The goal of our company is to offer and give the best solutions to the consumers in Malaysia. Nowadays, Malaysian tend to search for products with new technology that are easy and very convenient to use. The main product in this company is a ditty bag named The DotDitty Bag that comes out with a set of the multipurpose toothbrush that contain a toothpaste and 2in1 bottle pump. Our main target is travellers since the load of luggage or backpack is their main concern so, we solve the problems by making it easier for them to bring the toiletries set anywhere without any unwanted problems. The vision of our company is to be the gold standard of a globally successful business with a heart that will embolden business to better serve society and the mission is to offer all travellers at all range of the age and gender the best set of toiletries in terms of quality and safety. In order to achieve our vision and mission, we have made long term planning to maintain our brand and products in this industry. As time goes by, we will produce more products as the demand from the customers and improve the technology of the products.